The Balance of Power and the Balance of Payments (Tufts Archival Research Center, 2007)
The document was created from the speech, "The Balance of Power and the Balance of Payments," written by Walter B. Wriston for the U.S. Senate Subcommittee on National Security and International Operations on 13 May 1965. The original speech is located in MS134.001.001.00025.